Targeting Osteopontin, the Silent Partner of Na+/H+ Exchanger Isoform 1 in Cardiac Remodeling. Issue 9 (September 2015) - Mohamed, Iman A.; Mraiche, Fatima
Abstract : Cardiac hypertrophy (CH), characterized by the enlargement of cardiomyocytes, fibrosis and apoptosis, contributes to cardiac remodeling, which if left unresolved results in heart failure. Understanding the signaling pathways underlying CH is necessary to identify potential therapeutic targets. The Na + /H + ‐exchanger isoform I (NHE1), a ubiquitously expressed glycoprotein and cardiac specific isoform, regulates intracellular pH. Recent studies have demonstrated that enhanced expression/activity of NHE1 contributes to cardiac remodeling and CH. Inhibition of NHE1 in both in vitro and in vivo models have suggested that inhibition of NHE1 protects against hypertrophy. However, clinical trials using NHE1 inhibitors have proven to be unsuccessful, suggesting that additional factors maybe contributing to cardiac remodeling. Recent studies have indicated that the upregulation of NHE1 is associated with enhanced levels of osteopontin (OPN) in the setting of CH. OPN has been demonstrated to be upregulated in left ventricular hypertrophy, dilated cardiomyopathy and in diabetic cardiomyopathy. The cellular interplay between OPN and NHE1 in the setting of CH remains unknown. This review focuses on the role of NHE1 and OPN in cardiac remodeling and emphasizes the signaling pathways implicating OPN in the NHE1‐induced hypertrophic response. J. Cell. Physiol. 230: 2006–2018, 2015. © 2015 Wiley Periodicals, Inc.